Rečni meandri na kraških poljih - Černuta, Luka (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
River meanders present the most frequent planform of lowland rivers. Their formation on poljes mostly depends on flood water regime. Flooding dictates space-time zonation of meandering processes, of which the existence of active or passive phase of planform modification depends. Studied meanders of the stream Dobravka on the Radensko polje represent an excellent example of meanders (re)formed by meandering processes (inter)actions.
Keywords: kras (geologija); krasoslovje; kraška polja; meandri; poplavna območja; površinske vode; rečne struge; Slovenia; Slovenija